Operationalising access to oceanic fisheries resources by small-scale fishers to improve food security in the Pacific Islands. (February 2018) - Bell, Johann D.; Albert, Joelle; Amos, George; Arthur, Christopher; Blanc, Michel; Bromhead, Don; Heron, Scott F.; Hobday, Alistair J.; Hunt, Andrew; Itano, David; James, Philip A.S.; Lehodey, Patrick; et al.
Abstract: Maintaining the level of fish consumption in Pacific Island countries recommended for good nutrition as the populations of coastal communities grow, and as coral reefs are degraded by global warming and ocean acidification, will depend on small-scale fishers catching more tuna and other large pelagic fish. Concerted research and development by regional agencies shows that nearshore fish aggregating devices (FADs) provide one way for small-scale fishers to make this transition. Although the full potential of FADs remains to be assessed, several investments to optimise their use have been identified. These investments include pinpointing the locations where FADs are likely to make the greatest contributions to nutrition of coastal communities, integrating use of FADs with other livelihood activities, and improving the designs of FADs. Where Pacific Island countries have committed to developing nearshore FAD programmes, additional investments are needed to operationalise the use of FADs, particularly in cyclone-prone countries. These investments include: 1) training in safe and effective FAD-fishing methods; 2) developing reliable ways for forecasting when tuna, and other large pelagic fish (e.g., mahi mahi and wahoo), are likely to associate with FADs and delivering this information to fishers effectively; and 3) storing spare FAD materials, boats and fishing gear in cyclone-proof containers so that FADs lost during cyclones can be replaced quickly. When combined with measures to sustain catches of coastal demersal fish, operationalising the use of nearshore FADs is expected to help several Pacific Island countries attain the food security goals of regional policy frameworks. Highlights: Nearshore fish aggregating devices (FADs) are a practical way of increasing access to fish for rapidly-growing Pacific Island populations, and a prime adaptation to climate change. Optimising contributions of FADs to food security will depend on identifying the best locations for FADs, integrating the use of FADs with other livelihood activities, and improving FAD designs. Operationalising the use of FADs depends on assisting communities to fish safely and effectively around FADs, and replacing lost FADs quickly. Forecasting the distribution of tuna and other pelagic fish in coastal waters, and transmitting this information via 3G networks, will allow co-ordination of FAD-fishing trips with other livelihood activities. Forecasts of fish distribution based mainly on temporal variation in sea surface temperature are expected to be most useful to small-scale fishers in the near term.